Implementasi Pembelajaran Moral di Taman Kanak-Kanak Al Ihsan Bontang - Asiah, Siti Nor (Pascasarjana Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2019)
The research background is to find out the implementation of moral learning developed in the curriculum of Taman Kanak-kanak Al Ihsan Bontang on moral development of children and school competitiveness. The research objective is to describe the effort in the implementation of moral learning of the children at Taman Kanak-kanak Al Ihsan Bontang. The research methodology is using qualitative research method based on post positivism or interpretive philosophy, the naturalistic qualitative research methods that are inductive, the data obtained is qualitative data, which later will be interpreted so that the meaning is understood. The data collection techniques are interview, observation, and documentation. The research result shows that the implementation of moral learning at TK Al Ihsan Bontang has been planned to run properly, curriculum that is compiled until the birth of habituation activities is implemented to the students in daily implementation; such as pray for each other, Friday sharing, queued up in various things, care for each other, etc. make the atmosphere of learning and playing there becomes so good, the children seem to know their respective responsibilities and there is no rough treatment of friends his age, under him or to those who are more mature than his age. The teacher easily organizes the students and almost no students are unruly. Thus the desired achievement will not be difficult to be achieved and guided curriculum on Permendikbud no. 137 and no. 146 Year 2014 with 6 (six) aspects of development, will be easily achieved when the aspects of development to be achieved have been established for the activities that support the habituation so that children are unconsciously easily and with self-awareness applying and carrying out praiseworthy qualities.